Effects of Balance Training on Trunk Control and Postural Stability in patients with Sub-Acute Stroke - Aamir Gul Memon, Sadaf Naz, Mehjabeen Farooqui, Shoaib Ahmed Memon, Muhammad Imran Hussain, Rajni, Maryam, Bisma Sheikh (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the effects of balance training on trunk control and postural stability in patients with sub-acute stroke Methods: A randomized control trial study was carried out with a total of 60 stroke patients. Both males and females, aged above 40 years, were able to stand for at least 5 minutes without any support, and patients on grades 2, 3, and 4 on a scale of functional mobility were included in the study. Each group has a session of training for 40 minutes, 3 times per week for 6 weeks Berg Balance Scale was used for assessment. The valuation was done at baseline 3rd week and last 6th weeks. After 6 weeks of treatment, significant progress was recorded on Berg Balance Scale in both groups. BMI and nutritional status of the study population were also assessed. Results: The p-value of the balance error scoring system after the 6th week of treatment was (P=0.004) while at berg balance scale after the 6th week was (0.001), In group B, the p-value of the balance error scoring system after the 6th week of treatment was (P=0.001) while at berg balance scale after 6th week were (0.001), which showed significant results after 6th week of treatment. The p-value of the balance error scoring system between groups was at baseline 0.16 while after the 6th week of treatment was 0.001 and the p-value of the berg balance scale between the group was at baseline 0.764 while after the 6th week of treatment was 0.04. Both levels of the assessment indicated significant improvement in-between groups. In control group A (p=0.004) however, in the experimental group (p= <0.001), BESS also showed substantial development in both the experimental and control group with p-value (p<0.001) for each group. The results of the study population suggest that there is a strong relationship between obesity and stroke. Conclusion: This study evaluated that task-oriented balance training with sensory input indicated more progress in balance coordination and postural stability as compared to task-oriented balance exercises without sensory integration in patients with stroke Keywords: BMI, Postural Stability, Rehabilitation, Stroke